3D food printing for special needs: Ingredient development for texture-modified diets - Guedes, Jaqueline Souza (2025)
3D printing is an emerging technology in food production, experiencing growing interest and rapid development. It is especially promising for diets with special needs, such as dysphagia (a condition characterized by difficulty swallowing food). To achieve that, this technology requires the development of specific ingredients. The main objective of this PhD Thesis was to study and develop ingredients for 3D printing of foods with focus on dysphagic people. The gelling ingredients were based on the use of starches, given their widespread use, versatility, safety, and cost compared to other biopolymers. The Thesis was divided into two parts. The first part (Chapter 2 and 3) evaluated starch as a gelling ingredient with focus on the application described. Initially, starch from an unconventional source, uvaia seeds, was investigated, which presented a strong and plastic gel, with low suitability for 3D printing. Subsequently, in Chapter 3, maize starch was selected and modified by the dry heating technology (DHT), at different processing conditions. DHT improved the functional properties of maize starch, allowing for more continuous and smoother extrusion lines. A throughout characterization of starch granules, molecules and properties was conducted. Printed and molded gels were classified as level 5 (minced & moist) and level 6 (soft & bite-sized) by the International Dysphagia Diet Standardization Initiative (IDDSI). In the second part of the Thesis (Chapter 4 and 5), the focus was on developing more nutritious gels using pea protein and starch. In Chapter 4, pea protein and maize starch (native or modified by DHT) were used as gelling ingredients to produce acerola pulp gels. Printability, suitability for dysphagia diets, ascorbic acid content, and antioxidant capacity were evaluated. Gels containing starch (native or modified) and protein exhibited good extrusion and were compatible with IDDSI level 5. The presence of protein promoted greater antioxidant activity, a slight degradation of ascorbic acid, suggesting contributions from compounds present in the protein. Chapter 5 analyzed gels containing pea protein and wheat starch, either native or modified with DHT. It was observed that DHT also altered the structure of wheat starch, influencing the behavior of the gels when combined with the protein, especially depending on the dispersion medium. In tribology, the gels with modified starch had a higher coefficient of friction, and this value varied according to the dispersion medium and, especially, the applied pressure. Finally, it was found that the addition of starch, whether native or modified, did not compromise the bioaccessibility of pea protein. In conclusion, the Thesis demonstrates that DHT promotes specific modifications in starches, depending on the source, processing conditions, dispersion medium, and combinations with other ingredients. This modification can be applied in the development of personalized foods for dysphagia diets using 3D printing, with textural, functional, and nutritional properties tailored to the needs of the target public.